MMP-9 and TIMP-1 Promote Extracellular Matrix Remodeling in the Formation of Ovarian Endometrioma: in vitro Study on Chicken Chorioallantoic Membrane - Sari, Vidia; Jenie, Riris Istighfari; Widad, Shofwal; Dewanto, Agung (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: The invasion of endometrial tissue in the peritoneal layers is an important precursor to the formation of endometriosis. However, the mechanisms of the initial development of endometrioma remain unclear. This study aimed to explore the correlation between matrix metalloproteinase (MMP)-9 activity and tissue inhibitors of metalloproteinase (TIMP)-1 expression in the initial development of endometriosis through the invasion process of endometrial lesions in extracellular matrix (ECM) remodeling.METHODS: A total of 30 samples of endometrioma tissue were obtained from 24 women with endometriosis and examined at Dr. Sardjito General Hospital, Yogyakarta, Indonesia. The tissue was then implanted into a chicken chorioallantoic membrane (CAM) for five days to examine its invasion ability. The invasion scores were assessed using hematoxylin-eosin staining. MMP-9 activity and TIMP-1 expression were analyzed using gelatin zymography and western blot, respectively. The correlations between MMP-9 activity and TIMP-1 expressions with the invasion scores were analyzed using Spearman correlation tests with significance set as p<0.05.RESULTS: The results showed that there was a strong positive correlation between MMP-9 activity and invasion scores of endometriomas tissue (r=0.656; p=0.000). Meanwhile, expression levels of TIMP-1 had a weak negative correlation with the increase of invasion scores of endometrioma (r=-0.388; p=0.034). These results indicate the involvement of MMP-9 and TIMP-1 in the initial development of endometriosis during the ECM remodeling.CONCLUSION: MMP-9 activity and TIMP-1 expression were correlated with the invasion score of endometrioma tissue. This study provides evidence for understanding the mechanisms involved in ECM remodeling in the early process of endometriosis.KEYWORDS: endometrioma, extracellular matrix remodeling, MMP-9, TIMP-1